Comfort & joy : a fable - Hannah, Kristin (Ballantine Books, 2020)
Joy Candellaro, recently divorced and alone, boards a plane bound for the beautiful Pacific Northwest. When an unexpected detour takes her deep into the woods of the Olympic rainforest, Joy makes a bold decision to leave her ordinary life behind. In the small town of Rain Valley, six-year-old Bobby O'Shea is facing his first Christmas without a mother. Unable to handle the loss he has closed himself off from the world, talking only to his invisible best friend. His father Daniel is desperate to help his son cope. When the little boy meets Joy, the two begin to heal. --